2020
DOI: 10.3934/neuroscience.2020013
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy in pain management: New viewpoints and treatment targets based on a brain theory

Abstract: The current paper provides an explanation of neurophysiological pain processing based the Dimensional Systems Model (DSM), a theory of higher cortical functions in which the cortical column is considered the binary digit for all cortical functions. Within the discussion, novel views on the roles of the basal ganglia, cerebellum, and cingulate cortex are presented. Additionally, an applied Clinical Biopsychological Model (CBM) based on the DSM will be discussed as related to psychological treatment with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 203 publications
0
1
0
Order By: Relevance
“…According to the results of the research, it is found that the initial hypotheses are verified, as shown by other research in the past that has dealt with whether and how psychotherapy has the potential to be effective in matters of chronic pain and chronic illness (Jensen & Turk, 2014). On the one hand, psychotherapy provides a safe and supportive environment where patients can explore the emotional and psychological aspects of the pain they experience (Moss, 2020). On the other hand, it provides tools and techniques to deal with it, such as psychoanalytic therapy, cognitive-behavioral therapy and hypnotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…According to the results of the research, it is found that the initial hypotheses are verified, as shown by other research in the past that has dealt with whether and how psychotherapy has the potential to be effective in matters of chronic pain and chronic illness (Jensen & Turk, 2014). On the one hand, psychotherapy provides a safe and supportive environment where patients can explore the emotional and psychological aspects of the pain they experience (Moss, 2020). On the other hand, it provides tools and techniques to deal with it, such as psychoanalytic therapy, cognitive-behavioral therapy and hypnotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, considerable evidence suggests that clinical factors, such as the frequency and intensity of headache play a role in the analgesic response ( Affaitati et al, 2017 , Jesurum et al, 2012 ). On the other hand, migraine patients have higher risks of experiencing psychiatric comorbidities, such as anxiety and depression, which may develop into drug addiction, and in extreme cases even suicidal thoughts or actions ( Karimi et al, 2021 , Moss, 2020 ). Results from a previous cross-sectional study revealed that patients with medication-overuse headaches got higher scores representing anxiety and depression than their counterparts who did not overuse ( Cai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%